MEDIA MASSA DALAM MASYARAKAT PLURALIS - Pawito Pawito (Jurnal Ilmu Komunikasi, 2008)
This study attempts to scrutinize how mass media deal with pluralistic society and cul- ture. Some cases found in USA, England, and Australia are primarily examined first. The study then goes further to explore extensively what and how mass media in Indonesia deals with the issue of pluralistic society and culture. The study suggests that Indonesia’s mass media deal with this issue in a dynamic term from the period of New Order to post-reformation period.